Theses on Translation: An Organon for the Current Moment - Lawrence Venuti (Quaderns)
The theses offer a general theory of translation that encompasses the relation between theory and practice and the different models of translation that generate theoretical concepts like equivalence and ethics. The instrumental model that understands translation as a reproduction or transfer of a source-text invariant is critiqued, whereas a hermeneutic model that understands translation as an interpretation that varies the source text is advanced. Verbal choices are treated as interpretive moves that vary a range of textual features according to factors that are drawn decisively from the receiving culture where they are arranged in hierarchies of value. The interpretive act performed by translation is informed by global cultural hierarchies in which value is distributed unevenly across major and minor languages, redefining the ethical and political stakes of a translation project.